2008
DOI: 10.1136/jme.2007.023416
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitudes towards abortion: a UK study

Abstract: The percentage of pro-choice students was lower than that found in research on general practitioners' attitudes to abortion. It is unclear whether this is because students become more pro-choice as they progress through their medical career or because there is genuinely a change in attitudes to abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
23
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 14 publications
10
23
0
5
Order By: Relevance
“…This number is congruent with the results of the previous study of Irish medical students, where 58% of students reported that they would perform or would consider performing a legal abortion in their future careers 10. Similar studies carried out in the USA and Britain found that approximately 50% of students would be willing to perform an abortion 8 14 16…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This number is congruent with the results of the previous study of Irish medical students, where 58% of students reported that they would perform or would consider performing a legal abortion in their future careers 10. Similar studies carried out in the USA and Britain found that approximately 50% of students would be willing to perform an abortion 8 14 16…”
Section: Discussionsupporting
confidence: 87%
“…Notably, student attitudes did not change significantly as they progressed through medical school. UK-based studies have reported that up to two-thirds of medical students described themselves as ‘pro-choice’ 8. Cultural and religious influences were observed in a multicentre international survey involving medical students in Oslo, Norway and Belfast, North Ireland 9.…”
Section: Introductionmentioning
confidence: 98%
“…Outras pesquisas, realizadas em países com legislação mais liberal do que a brasileira, demonstraram que a intenção dos estudantes em participar do aborto é influenciada pelas circunstâncias da gravidez. No Reino Unido, um levantamento em 2008 mostrou que 67% dos estudantes fariam o aborto em caso de risco de morte da mulher, 59% fariam em caso de gravidez por estupro e apenas 37% o fariam em caso de gravidez indesejada 13 . Dados diferentes foram obtidos entre estudantes da Espanha, entre os quais 86% disseram que teriam disponibilidade para participar do aborto por estupro 14 .…”
Section: Discussionunclassified
“…As categorias de respostas para as seções B e C foram "sim" ou "não". O questionário foi desenhado levando em consideração estudos prévios sobre atitudes e opiniões sobre o aborto entre médicos e estudantes de Medicina 8,11,13 .…”
Section: Coleta De Dadosunclassified
“…Consider termination of pregnancy: this remains a divisive and stigmatising issue for doctors 2 and society 3 but is frequently included on the medical summary list. What might a chance disclosure on a computer summary have on family relationships?…”
mentioning
confidence: 99%